Estudio de factibilidad para la instalación de una fábrica de calzado femenino industrializado cantón Quevedo año 2015 - Montecé Vélez, Víctor Eduardo (2016)
This research project was made in Quevedo, in order to determine a feasibility study for the installation of an industrialized women's footwear factory. The project analyzes the current problems and through diagnosis, causes and effects of the current identified Situation. The purpose of research is to develop a feasibility study for the installation of a women's footwear industrial factory in Quevedo in 2015. Stores in Quevedo are supplied mainly with footwear produced in other places like Quito, Guayaquil and Ambato. There are not firms engaged in this activity in the town and the cost involved to bring them is high. So, the company of women's footwear will aim to produce enough footwear at reasonable prices for the benefit of the local consumers. A feasibility study will create positive administrative and financial processes for the operation of the plant. It will help to have actual financial reports on production processes that will allow to grow effectively and competitively in the short term with the possibility that the owner, customers and the general population benefit through the generation of jobs. The methods used in this research project were deductive, inductive, and analytical. The results are shown by the market study, with the attractive potential unmet demand for the intended product. The development of the technical study identified the optimal size and location of the plant, as well as, technology and inputs necessary for the production process of the company. The economic and financial viability study shows this project has profitability during its lifetime allowing it to grow in the short, medium and long terms. The most relevant conclusions and recommendations of this research are based on the research on the objectives and the results picked up from the survey and tables.